Kinetics and Mechanism of Oxidation of t-Butylbenzylamine by Diperiodatoargentate(III) in Aqueous Alkali - Mahantesh A. Angadi; Suresh M. Tuwar (E-Journal of Chemistry)
t-Butylbenzylamine (t-BA) is used as a free base in the synthesis of salbutamol drug. Its mechanism of oxidation was proposed from kinetic studies. The kinetics of oxidation of t-butylbenzylamine by diperiodatoargentate(III) (DPA) was studied spectrophotometrically by monitoring decrease in absorbance of DPA. The reaction was found to be first order each in [DPA] and [t-BA]. The effect of alkali concentration in a wide range on rate of reaction was studied. The rate of reaction was found to be increased with increase in [OH–] in the lower range of [OH–], decreasing effect in the middle range and at higher range again increasing effect on rate of reaction was observed. The added periodate retarded the rate of reaction. The polymerization test revealed that oxidation was occurred with the intervention free radical. A suitable mechanism was proposed for a middle range of [OH–]. The active species of silver(III) periodate for all the three different stages of [OH–] are assayed. Rate law was derived and verified. The oxidative product of t-BA was characterized by LC-ESI-MS spectra.